REPRESENTATION OF GENDER EQUALITY ON JOKOWI’S INSTAGRAM POST: CHARLES S. PEIRCE’S SEMIOTICS THEORY - Shohihuzzihni Shohihuzzihni (Asosiasi dosen IDEBAHASA KEPRI, 2022)
Men and women were sometimes still considered differently by some people in society. There were some beliefs spreading that women could not afford anything done by men in every sector of life. Participating people in Politics in Indonesia was still inequal between men and women. To tackle this issue, media needed to take action in promoting gender equality. Social media, however, currently became usable to access the information or the entertainment. Instagram, for example, as one of media used by massive people in the world created an alternative way to build public pattern and norms, more over the users were those who had a powerful role in shaping public opinion which one of them was such as a president. Joko Widodo, the president of Indonesia, had posted many contents including video, photograph or digital image, like digital image which attract society to its uniqueness, and it potentially gave influences to his followers looking at his position as a president as well. This research aims to discover the sign representation of gender equality in posts including image and caption used on the Instagram based on Peirce’s theory analysis on the account @jokowi. Peirce classified signs into three which are icons, indexes and symbols. The approach used in the research was qualitative that focus on analyzing data in forms of image and text. The result of the research shows that the discoveries of sign representation on Jokowi’s post represented gender equality much better than inequality which is found in the same post in icons and symbols.